Os instrumentos de financiamento às Empresas de Base Tecnológica no Brasil - Pereira, Rosângela Cristina de Carvalho (Universidade Federal de São Carlos, 2007)
This dissertation has as central objective to analyze to what extent the available financing instruments for Technological Based Firms (EBTs) in Brazil, are adjusted to the purpose of promote the creation and development of this type of company. This implies, first of all, to carry through a survey and the characterization of extant public and private specific financing forms in the country. Thereafter, through the sample of EBTs searched, to evaluate empirically, the critical opinions, and suggestions presented by the entrepreneurs regarding to the current fomentation lines. The EBTs are technologically dynamic companies, with a dense knowledge base that carry through radical or incremental technological innovations in national or international scope. These innovations carry out the central role of these companies. As they are companies based on the technological development, the EBTs have specific functioning characteristics. These companies main aspect is the technological development, which causes in the majority of the cases, the lack of tangible assets that can serve as guarantees in the attainment of conventional credits. Thus, the EBTs needs highly specialized human capital and an initial financial resource for the research and the development given that, in this phase generally the companies still don't have commercialized products and, consequently, positive cash flow to guarantee its sustentability. Resulting from these specificities, the EBTs located in peripheral economies face other obstacles jointed to the macroeconomic environment, as raised basic taxes of interests, incipient market capital, raised competition of transnational companies, small extension of the markets, not consolidated systems of innovation, lack of joint in federal level of the governments to the innovation and technological development incentive of each country. In relation to the private financing, it is boarded the venture capital funds, a financing modality widely used in some countries, as United States and Israel. In these countries this modality is well succeed. However, the intense active role of the governments in articulation and promotion of this industry in both cases is observed. It is also dialed with the election and monitoring costs with the enterprises selected by venture capital funds. To explain this relationship, the Agency Theory is utilized, in which the relationship between the Investor and the Entrepreneur is complicated by the lack of transparency between the entrepreneurs and the risk investors and also by the availability of information in this relationship. Beyond the described difficulties, in Brazilian case, the venture capital faces difficulties regarding to the legal guarantees in the effective investments, therefore the Brazilian legal environment still does not promote adequate corporative governance. Thus, the legal environment of the country also affects the getting of capital for this modality. Finally, the results and the analyses on the EBTs behaviors in Brazil in the studied period are pointed, from the empirical research, and the profile of this EBTs are traced as well as its demand for financing.
Keywords: Inovações tecnológicas; Inovação - gestão; Inovações tecnológicas aspectos econômicos; ENGENHARIAS::ENGENHARIA DE PRODUCAO